Efektifitas model pembelajaran problem based learning dengan media animasi terhadap motivasi belajar siswa pada materi asam basa - Hamsyah, Eka Fitriana; Gustina (Universitas Papua, Manokwari, Indonesia, 2025)
More abstract chemistry learning makes students have difficulty understanding the concept, making them less motivated to follow the learning. This research aims to determine whether or not the problem-based learning model with animation media effectively increases students’ learning motivation. The research methodology is one group pretest-posttest. The research instrument is a student learning motivation questionnaire comprising 15 statement items covering enthusiasm, confidence, satisfaction, and attention indicators. The hypothesis was tested with SPSS through a paired sample T-Test. The study results showed a significance value of .000> 0.005, concluding that the problem-based learning model with animation media effectively increases students’ learning motivation. Based on the results of this research, it is recommended that teachers and educators use student-centered learning models, such as problem-based learning, to increase students’ learning motivation. In addition, it is necessary to develop programs to increase students’ awareness and confidence to improve their academic achievement.